SPECIFIC FEATURES OF ECONOMIC AND EXCHANGE INTEGRA- TION OF AFRICAN COUNTRIES - I.N. EFREMENKO (Advanced Engineering Research)
The analysis of the basic tendencies of economic, financial and monetary integration in the African region is given. Research confirms necessity and urgency of theoretical study of these questions.